Geophysical evidence for gas hydrate accumulation related to methane seepage in the Taixinan Basin, South China Sea. (December 2018) - Wang, Xiujuan; Liu, Bo; Qian, Jin; Zhang, Xin; Guo, Yiqun; Su, Pibo; Liang, Jinqiang; Jin, Jiapeng; Luan, Zhendong; Chen, Duanxin; Xi, Shichuan; Li, Chaolun
Graphical abstract: Highlights: Seafloor images showed the activity differences of fluid seepage for each cold seep. The impedances reveal the occurrences and saturation of hydrate and free gas at cold seeps. Geophysical and geological data are combined to show the evolution stages of cold seep. Abstract: Seafloor features, seismic amplitude anomaly, geophysical attributes, and chemosynthetic community are different in the methane seepage areas of Taixinan Basin, South China Sea. We integrate the new acquired seafloor images with seismic data to present the differences of three cold seeps which are associated with fluid flows. These three cold seeps include two inactive sites (CS02-8 and CS02-9) and one active site (Site F). At site CS02-8 area, the seafloor carbonate and buried carbonate layer are identified from core samples at Site GMGS2-08. BSR is interrupted by the upward migration of fluids from the base of gas hydrate stability zone (BGHSZ) and gas hydrate-bearing sediments show pull-up seismic reflections below the buried carbonate layer. At site CS02-9 area, near seafloor carbonate was found at hole GMGS2-09B where a 62 m-high pinnacle and gas hydrate were also found from the core samples. The LWD data at hole 09A indicate that free gas is present below the depth of 64 m without gas hydrate. The average saturations of free gas estimated from P-wave velocity are about 3% with a patchy distribution and 0.3% with homogenous distribution respectively, which is accord with the enhanced reflection below BGHSZ. At Site F area, the exposed gas hydrate, carbonate and flourishing chemosynthetic communities are detected using ROV with a high amplitude seismic reflection at seafloor. The BSR is interrupted by a chimney structure from the seismic data which indicates that the fluids are migrating vertically and rise to the seafloor as gas bubbles. The geophysical evidence at these three seep sites show that pore-filling gas hydrates with saturations ranging from 10% to 40% are widely distributed above the BSR. However, massive or vein gas hydrates only occur around cold seeps.